Ecophysiological adaptations of coexisting Sphagnum mosses - Hájek, Tomáš (Jihočeská univerzita, 2008)
I studied ecological and physiological adaptations of peat misses (Sphagnum species) coexisting along the environmental gradients in mires. Production, decomposition, water relations, desiccation tolerance and nutrient economy of Sphagnum species were evaluates along the hummock-hollow gradient of water table, while the light adaptations were assessed in an open and forested mire.
Ecophysiological adaptations of coexisting Sphagnum mosses